Military expenditure and economic growth: evidence from a heterogeneous panel of African countries - Charles Shaaba Saba (Ekonomska Istraživanja, 2019)
This study investigates the causal relationship between military expenditure and economic growth by using a balanced panel of 35 African countries spanning 1990 to 2015. It uses the more recently developed bivariate heterogeneous panel causality, GMM and SGMM estimation techniques. The country-by-country causality results reveal:(i) no causal relationship between military expenditure and growth in seven countries; (ii) unidirectional causality from military expenditure to growth in two countries; (iii) unidirectional relationship from growth to military expenditure in fourteen countries; and (iv) bidirectional relationship in twelve countries. These findings imply: (i) that the seven African countries with no causality can pursue defence policy objectives independently from growth policy objectives; (ii) in the fourteen countries, the fact that growth causes military expenditure and not vice versa implies that, defence decisions are not made in a way as to relatively promote growth; (iii) two African countries effectively use military expenditure for growth aims, hence military expenditure causes growth; and (iv) the bidirectional causality in the 12 countries implies that both growth and defence policy objectives can be pursued together. The GMMs results show that military expenditure has a significant negative impact on growth in Africa.